THE EFFICIENCY OF CRUDE CORROSION INHIBITOR AND GAS CORROSION INHIBITOR BY USING CARBON STEEL 1018 WITH POLARIZATION METHOD - puji astuti ibrahim (Journal of Green Science and Technology, 2020)
Carbon Steel 1018 is a low carbon steel having a carbon content (C) of 0.14-0.20% (<0.30% C). Low carbon steel is commercially known as mild steel. Corrosion is one way to prevent corrosion caused by the environment. Corrosion inhibitor are taken between the Crude Corrosion Inhibitor and Gas Corrosion inhibitor on Carbon Steel 1018 using the polarization method. Corrosion inhibitors work by making passive layers in the form of thin films or films on the surface of the material used as a barrier between metals and corrosive media. The analysis method used is polarization. Inhibition Efficiency Results obtained for Gas Corrosion Inhibitors (1A) at 10 ppm 96.86%, 20 ppm 59.74%, 30 ppm 74.48%. The Crude Corrosion Inhibitor (2A) results obtained inhibition efficiency for 10 ppm 99.57%, 20 ppm 77.69%, and 30 ppm 12.63%. The optimum value for the Gas Corrosion Inhibitor and Crude Corrosion Inhibitor is at 10 ppm at 96.86% and 99.57%. Keywords: carbon steel,crude corrosion inhibitor, corrosion , gas corrosion inhibitor, inhibitor